Meningkatkan Kualitas Hidup Lansia Melalui Arsitektur Terapeutik Studi Kasus Griya Usia Lanjut Santo Yosef - Tia Aisyah Maharani; Sri Suryani Yuprapti Winasih (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
Every human being needs a pace to shelter, engage in activities, spend time, and socialize in their daily lives, including those who have reached old age. Griya Usia Lanjut Santo Yosef is established for those in need of care and social support in their elderly lives. Typically, those who reside in these facilities who lack a partner or have healthy issues, thus requiring significant impact on their well-being. The quality of the environment within nursing homes is crucial considering that the elderly often face complex challenges such as declining mental health, dementia, loneliness, minmal social activity exacerbating their physical and mental conditions. Therapeutic architecture is an architectural approach focusing on users by creating built environments that foster physiological and psychological interaction. This research explores principes of therapeutic architecture such as open space, accessibility, natural lighting, spatial flexibility to support residents recovery and enhance the quality of life for the elderly.